ANALISIS KESELAMATAN DAN KESEHATAN KERJA (K3) MENGGUNAKAN METODE HAZARD AND OPERABILITY STUDY (HAZOP) DI PT. RODA PASIFIK MANDIRI - Ahmad Fauzan; Andung Jati Nugroho (CV. KAMPUS AKADEMIK PUBLISING, 2024)
PT Roda Pasifik Mandiri is a manufacturing company engaged in the bicycle manufacturing industry so that the risk of work accidents is quite high. This research discusses the analysis of Occupational Safety and Health (K3) using the Hazard And Operability Study (HAZOP) method. The purpose of this study is to identify the potential hazards of work accidents, provide a risk assessment of the hazard sources contained in the E-Bike production area of PT Roda Pasifik Mandiri and provide recommendations for improvements to hazard sources that have extreme and high risk values. Data analysis using descriptive data analysis method with HAZOP. The results showed that there are 8 potential and sources of hazards found in the E-Bike production area of PT Roda Pasifik Mandiri. Based on the risk assessment, it shows that the risk of hazard sources in the E-Bike production area of PT. Roda Pasifik Mandiri includes Extreme Risk, namely at the pointed corners of the frame, High Risk, namely in the cutter blade, gerindra machine, and worker attitude. Moderate Risk is on bicycle frames, raw material cartons piling up, impact machines and compressor dust.